Production analysis and fish betutu marketing (Oxyeleotris marmorata) in Polombangkeng Utara Sub-District,Takalar District - Haj, M. Hairul; Adhawati, Sri Suro (Torani Journal of Fisheries and Marine Science, 2019)
Polombangkeng Utara sub-district is one of the sub-districts that has a large potential of capture / land fisheries, with potential capture fisheries data in 2016 amounting to 3,827 tons. This has led to the emergence of microbial fishing businesses that can increase income and welfare of fishermen. Marketing and investment are the biggest obstacles in this fishing effort. The purpose of this study was to determine how much production and opinions of fishermen and marketing of betutu fish. This research was conducted in September 2018 to October 2018. The method used was descriptive qualitative and quantitative by using a questionnaire. The sampling method used was the random sampling method with a total sample of 22 people, of which 14 were fishermen, 6 fishermen were fishing, 1 was a collecting trader and 1 was an exporter. The data analysis used is profit analysis and marketing analysis. The results of the research obtained are the average profit per trip obtained by fishermen bubu Rp. 264,506, - higher than the average profit per trip fishermen fishing for Rp. 41,711, -, while the average profit per trip obtained by collecting traders is Rp. 257,404, - and exporters of Rp. 638,669, -. And the highest marketing margin is found in the marketing channel 2 at the marketing marketing agency, which is Rp. 130,000, and the lowest marketing margin is in the marketing channel 2 at the distributor marketing agency of Rp. 10,000, -. The highest marketing costs incurred by marketing institutions are found in the marketing channel 2 at the marketing marketing agency, which is Rp. 70,000, and the lowest marketing costs are in the marketing channel 2 at the distributor marketing agency of Rp. 6,000, - and the most efficient marketing efficiency is found on channel 2, which is 0.027%. Keywords: Betutu Fish, Bubu Fishermen and Pool and Line, Production, and Marketing